2005
DOI: 10.2193/0022-541x(2005)069<0332:fgsaso>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Scale Genetic Structure and Social Organization in Female White-Tailed Deer

Abstract: Social behavior of white-tailed deer (Odocoileus virginianus) can have important management implications. The formation of matrilineal social groups among female deer has been documented and management strategies have been proposed based on this well-developed social structure. Using radiocollared (n = 17) and hunter or vehicle-killed (n = 21) does, we examined spatial and genetic structure in white-tailed deer on a 7,000-ha portion of the Savannah River Site in the upper Coastal Plain of South Carolina, USA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 45 publications
(66 reference statements)
3
51
0
Order By: Relevance
“…Furthermore low female dispersal should not be assumed for all areas. High female dispersal rates have been reported in areas with heavy annual harvests and a young female age structure (Comer et al 2005), as well as in fragmented agricultural landscapes (Nixon et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore low female dispersal should not be assumed for all areas. High female dispersal rates have been reported in areas with heavy annual harvests and a young female age structure (Comer et al 2005), as well as in fragmented agricultural landscapes (Nixon et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Forest regeneration sites located in remote areas where access to the hunting public is difficult or problematic also may benefit from an application of localized management prior to timber harvesting to ensure successful regeneration (Campbell et al 2004). However, effectiveness of any behavior-based management technique may be limited by the behavioral plasticity of white-tailed deer (Miller 1997, Comer et al 2005. Campbell et al (2004) assessed the feasibility of implementing localized management on a hunted, nonmigratory, and high-density deer herd in the central Appalachian Mountains of West Virginia, USA, and reported that the a priori assumptions of localized management were met and that a test of localized management on the study site would be possible.…”
mentioning
confidence: 99%
“…Hunting was either done by stalking or by using dogs to drive deer to stationary hunters, and we assumed that kill locations were situated within the normal home range of the animals. Using kill locations from drive hunts did not bias the conclusions in a study of fine-scale genetic structure of white-tailed deer, Odocoileus virginianus (Comer et al 2005).…”
Section: Study Area and Sample Collectionmentioning
confidence: 98%
“…Inclusion of juveniles potentially biases results towards greater correlation between spatial and genetic distances (Coltman et al 2003;Comer et al 2005). Due to sample size limitations in our data set, we mainly had to perform analyses that included the juveniles, although some analyses were performed on adults alone (see "Results").…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…The validation study of Anderson et al (2002) included markers BM848, BM6506, and BM4208, and while H O was <H E for all three, the authors conclude that "little evidence exists of null alleles at these loci", with a recommendation for use in studies of gene flow and parentage (Anderson et al, 2002). Moreover, markers BM4208 and BM6505 continue to be employed in studies of kinship and relatedness (Grear et al, 2010), despite demonstrated HWE deviations (Anderson et al, 2002;Comer et al, 2005) and inconsistent genotypes (DeYoung et al, 2003a) in deer populations across the US. To prevent data bias and biological misinterpretations, markers need to be assessed thoroughly with each novel application.…”
Section: Genotyping Errorsmentioning
confidence: 99%